Literature Review: Characteristics of Digital Leadership in Digital Transformation - Ridha, Rizkillah; Susanto, Tony Dwi; Subriadi, Apol Pribadi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Digital transformation has recently created significant research interest due to its acceleration across industry sectors. However, the existing literature on digital transformation that addresses digital leadership characteristics is insufficient to provide a comprehensive understanding. This research explores the characteristics, traits, and skills of digital leadership. The research methodology used a systematic literature review summarizing 30 articles from Scopus-indexed journals. Characteristics are obtained from citations from previous research that discusses digital transformation leadership. The results of this study explain that digital leadership characteristics consist of twenty different traits, seven of which are characteristics of digital leaders that are important for the effective implementation of digital transformation. As such, these characteristics can reflect the significance of digital leaders in achieving digital transformation goals at the human and organizational levels.